Educational Word Box Game Tool To Enhance Cognitive Development In Early Childhood - Nurqodriah, Yuyu; Widjayatri, RR. Deni; Mercury Kiwonde, Flora (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This study aims to investigate the improvement of cognitive abilities in early childhood by utilizing the educational game